Phenotypic appearances of prostate utilizing PET-MRI and PET-CT with 68Ga-PSMA, radiolabelled choline and 68Ga-DOTATATE. Issue 3 (March 2018) - Haroon, Athar; Afaq, Asim; Nuthakki, Soujanya; Freeman, Alex; Biassoni, Lorenzo; Fanti, Stefano; Beheshti, Mohsen; Jan, Hikmat; Vinjamuri, Sobhan; Emberton, Mark; Bomanji, Jamshed
Abstract : The objective of this study was to highlight the role of multimodality imaging and present the differential diagnosis of abnormal tracer accumulation in the prostate and periprostatic tissue. Our departments have performed molecular imaging of the prostate utilizing PET-CT and PET-MRI with a range of biomarkers including 18 F-FDG, radiolabelled choline, 68 Ga-DOTATATE PET-CT and 68 Ga-PSMA images. We retrospectively reviewed the varying appearances of the prostate gland in different diseases and incidental findings in periprostatic region. The differential diagnosis of pathologies related to prostate and periprostatic tissue on multimodality imaging includes malakoplakia, rhabdomyosarcoma, lymphoma, prostate cancer, neuroendocrine tumours, uchida changes, rectoprostatic fistula, synchronous malignancies, lymphocoele and schwanoma. There exists a wide differential for abnormal tracer accumulation in the prostate gland. As a radiologist and nuclear medicine physician, it is important to be aware of range of prostatic and periprostatic pathologies. Abstract : Supplemental Digital Content is available in the text.